Die kausalen Verknüpfungsmittel des Deutschen und des Italienischen. Eine kontrastive Beschreibung unter formalem und funktionalem Aspekt - Ballestracci, Sabrina (Linguistik Online, 2011)
This paper is a contrastive description of the causal grammatical structures mentioned in five grammar books of German and four grammar books of Italian. The study is inspired by the results of a previous empirical research upon the causal connectors denn, weil, da in German and perché, poiché, siccome in Italian, which has demonstrated that there are many similarities, but without any complete correspondence between the analyzed German and Italian grammatical structures. The purpose of this work is to verify if this thesis holds true not only for a limited number of connectors, but also for the whole system of German and Italian causal structures. The study is based upon a broad concept of causality, seen as the question about "why and with which purpose do events und states happen and verify". It focuses not only on the grammatical structures which are traditionally defined causal, but also on final and conditional structures. The results of the research are summarized at the end of the paper with the expectation that they will be helpful to the didactic transmission of the German causal structures with Italian learners.